In vitro stimulation of pancreatic enzyme discharge by calcium. Issue 10 (October 1987) - Layer, P; Hotz, J; Cherian, L; Goebell, H
Abstract : The mechanism for acute hypercalcaemia increasing pancreatic enzyme secretion is unknown. To determine if raised extracellular calcium concentrations can directly stimulate pancreatic enzyme output, we measured discharges of pulse labelled protein and chymotrypsin from isolated cat pancreatic lobules in the presence of normal and raised calcium concentrations. Incubation in 5.0 mmol/l calcium increased discharges of pulse labelled protein (four fold), chymotrypsin (2.5 fold) and amylase (2.2 fold), compared with control experiments with 2.5 mmol/l calcium (p less than 0.001). This effect was similar to the maximal effect of carbachol or caerulein. Compared with 5.0 mmol/l calcium, incubation at the higher calcium concentration of 10.0 mmol/l induced similar discharges of chymotrypsin and amylase, whereas the increase in discharge of pulse labelled protein was smaller (p less than 0.01). The effects of raised calcium were not altered by atropine. Incubation in a high calcium medium did not impair pancreatic acinar response to subsequent stimulation with carbachol, but incubation in hypothermia abolished the effects of high calcium concentrations, suggesting that increased enzyme discharge is caused by stimulation of secretion not to cell damage. These data are consistent with a direct stimulatory effect of raised extracellular calcium concentrations on pancreatic acinar cell function.